Primary Allograft ACL Reconstruction in Skeletally Immature Patients—A Systematic Review of Surgical Techniques, Outcomes, and Complications - Shanmugaraj, Ajaykumar; de SA, Darren; Skelly, Matthew M.; Duong, Andrew; Simunovic, Nicole; Musahl, Volker; Peterson, Devin C.; Ayeni, Olufemi R. (The Journal of Knee Surgery, 2019)
The purpose of this systematic review is to ascertain the risk profile of allografts in primary anterior cruciate ligament reconstruction (ACLR) of skeletally immature patients. Three databases (PubMed, EMBASE, and MEDLINE) were searched for articles addressing primary ACLR in skeletally immature patients (i.e., open femoral and tibial physes). Inclusion criteria encompassed the use of allograft tissue with available postoperative outcomes data. The methodological index for non-randomized studies (MINORS) was used to assess all studies. Descriptive statistics such as means, 95% confidence intervals and standard deviations are presented where applicable. A total of 3,852 studies were screened, with 9 studies of a total of 406 skeletally immature patients (mean age 14.9 ± 1.2 years) satisfying inclusion criteria. The majority (98%) of included patients underwent complete transphyseal ACLR. Where specified, allograft options included Achilles tendon (AT) (66.5%), tibialis anterior tendon (7.6%), bone–patellar tendon (2.5%), and fascia lata (1.0%). The use of a bone block for the AT was reported in one patient (0.2%). Postoperatively, and where specified, patients achieved full range of motion (12.1%), had good Lysholm scores of 94 to 100 (8.1%), and a return to preinjury level athletic participation of 82.9% (8.4%). Complications (13.3%) included graft failures (7.9%), nonrevision reoperation (4.7%), and a combined leg length discrepancy and angular (valgus and extension) deformity (0.2%). There were no reported incidences of disease transmission. Although failure rates of primary allograft ACL reconstruction are acceptable compared with other studies of mainly autograft use in this young, high-risk population, there was a very low rate of clinically significant physeal damage. However, the relatively low quality of the included studies limits the ability to recommend routine use of allograft for ACLR in the skeletally immature patient. More robust studies with long-term follow-up data are necessary to better ascertain the influence of allograft choice on postoperative outcomes for these young patients. This is a Level IV study, systematic review of Levels III and IV studies.
Keywords: allograft; pediatric; anterior cruciate ligament; knee; skeletally immature